Selection of Promising Pumpkin Varieties For Re-Cultivation - Toramatov R.G; Shokirov A.J.; Abdurashidov I.D. (Zien Journals, 2023)
In 2022-2023, 4 varieties and 8 lines were planted and the growth, development and productivity of plants were studied in order to select promising varieties for re-cultivation of crops. The regional variety Shirintoy served as the standard. On June 10, 25-day-old seedlings of pumpkin varieties were planted on an experimental field with a pattern of 280×70/2×70 cm. In 2022-2023, the marketable yield of the total harvest was 31.0 t/ha or 87.0% for the Shirintoy variety (st) , while the highest marketable yield was in - L-9 (43.2 t/ha) - 87.6%, L-14 (41.3 t/ha) - 85.6%, L-10 (39, 9 t/ha) - 85.0%, Ushiki Kuri (42.5 t/ha) - 88.5% and Ulybka (32.8 t/ha) - 92.0%. in varietal samples
Keywords: pumpkin growing; vegetable; farmers; agriculture